2017
DOI: 10.1038/bjc.2017.289
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine dehydrogenase pharmacogenetics for predicting fluoropyrimidine-related toxicity in the randomised, phase III adjuvant TOSCA trial in high-risk colon cancer patients

Abstract: Background:Dihydropyrimidine dehydrogenase (DPD) catabolises ∼85% of the administered dose of fluoropyrimidines. Functional DPYD gene variants cause reduced/abrogated DPD activity. DPYD variants analysis may help for defining individual patients’ risk of fluoropyrimidine-related severe toxicity.Methods:The TOSCA Italian randomised trial enrolled colon cancer patients for 3 or 6 months of either FOLFOX-4 or XELOX adjuvant chemotherapy. In an ancillary pharmacogenetic study, 10 DPYD variants (*2A rs3918290 G>A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 34 publications
7
53
1
4
Order By: Relevance
“…Our data confirmed the association between the c.2194G>A SNP and severe toxicity (Table 3), and resulted in line with both the PETACC8 and TOSCA studies in terms of the significant correlation with haematologic toxicity. 23,24 In particular, we found a statistically significant association between this SNP and severe neutropenia, which was observed in 50% of the patients carrying c.2194G>A (23 out of 46) vs. 21% of the patients with WT genotype (67 out of 320) (p < 0.0001).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Our data confirmed the association between the c.2194G>A SNP and severe toxicity (Table 3), and resulted in line with both the PETACC8 and TOSCA studies in terms of the significant correlation with haematologic toxicity. 23,24 In particular, we found a statistically significant association between this SNP and severe neutropenia, which was observed in 50% of the patients carrying c.2194G>A (23 out of 46) vs. 21% of the patients with WT genotype (67 out of 320) (p < 0.0001).…”
Section: Discussionmentioning
confidence: 60%
“…The clinical impact of c.2194G>A SNP is still controversial, although recent studies have shown promising relevance in the correlation with fluoropyrimidine-related toxicity. 5,[23][24][25] In the pharmacogenetics analysis on 927 patients of the QUASAR II trial, 19 c.2194G>A variant was not found to be associated with fluoropyrimidine toxicity although it should be considered that this study was performed in patients treated with capecitabine mono-chemotherapy only.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations